2020
DOI: 10.25077/jka.v8i4.1092
|View full text |Cite
|
Sign up to set email alerts
|

Pelaksanaan Program Inisiasi Menyusu Dini Di Wilayah Kerja Puskesmas Lubuk Buaya Kecamatan Koto Tangah

Abstract: Inisiasi menyusu dini (IMD) atau early latch on adalah kesempatan yang diberikan kepada bayi segera setelah lahir dengan cara meletakkan bayi di perut ibu, kemudian dibiarkan untuk menemukan puting susu ibu dan menyusu hingga puas. Tujuan: Mendeskripsikan pelaksanaan program IMD di wilayah kerja Puskesmas Lubuk Buaya kecamatan Koto Tangah. Metode: Penelitian ini merupakan evaluation research dengan pendekatan kualitatif menggunakan strategi management-oriented systems models, dengan 4 informan utama dan 9 info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…The better the husband's support given to the mother during maternity can increase the motivation of the mother to do the EIBF as soon as the baby is born (31) Based on Table 6 it was found that health services provided by midwives or nurses on the success of the implementation of early breastfeeding are still found in several obstacles in the procedure for implementing EIBF, and breastfeeding policies that are friendly to maternal and infants, that the implementation of the EIBF has not been running optimally because there is no good division of tasks, to cause burden work on midwives and nurses in providing labor care (34). The unavailability of a clear standard operational procedure (SOP) related to the implementation of EIBF carried out by midwives and nurses, so there are no EIBF practice procedures that explain in detail related to the division of tasks in health workers in the success of EIBF practices in maternity and breastfeeding mothers (35).…”
Section: Discussionmentioning
confidence: 99%
“…The better the husband's support given to the mother during maternity can increase the motivation of the mother to do the EIBF as soon as the baby is born (31) Based on Table 6 it was found that health services provided by midwives or nurses on the success of the implementation of early breastfeeding are still found in several obstacles in the procedure for implementing EIBF, and breastfeeding policies that are friendly to maternal and infants, that the implementation of the EIBF has not been running optimally because there is no good division of tasks, to cause burden work on midwives and nurses in providing labor care (34). The unavailability of a clear standard operational procedure (SOP) related to the implementation of EIBF carried out by midwives and nurses, so there are no EIBF practice procedures that explain in detail related to the division of tasks in health workers in the success of EIBF practices in maternity and breastfeeding mothers (35).…”
Section: Discussionmentioning
confidence: 99%
“…Pemberian ASI juga menjadi bentuk perawatan ibu dan pemberian nutrisi sejak dini yang dapat mengurangi resiko stunting (Nurnainah & Asikin, 2019). Inisiasi Menyusu Dini (IMD) merupakan program dari Departemen Kesehatan Republik Indonesia, berupa rangsangan awal yang dimulai dengan pemberian Air Susu Ibu (ASI) secara dini dandiharapkan berlanjut hingga enam bulan pertamakehidupan bayi (Faisal et al, 2020).…”
Section: Hasil Dan Pembahasan Hasilunclassified
“…Research has shown that EIB is one way to stimulate the posterior pituitary gland to secrete oxytocin so that the uterus contracts. EIB is a process of providing an opportunity given to the baby immediately after birth by placing the baby on the mother's stomach, then allowing it to find the mother's nipple and suckle until satisfied (Diba Faisal et al, 2020). EIB followed by continuous breastfeeding increases adequate uterine contractions, thereby accelerating uterine involution (Delli Carpini et al, 2019;Dixon et al, 2013).…”
Section: Introductionmentioning
confidence: 99%